2015
DOI: 10.1287/orsc.2015.0984
|View full text |Cite
|
Sign up to set email alerts
|

Driving Performance via Exploration in Changing Environments: Evidence from Formula One Racing

Abstract: Until recently, scholars have customarily lumped multiple dimensions of environmental change into single constructs, and usually ascertained that the more the context changes, the more value firms derive from higher levels of exploration. In sync with more recent studies focusing on specific dimensions of change, in this paper we borrow theoretical elements from systems theory to examine the possibility that the reward to developing innovative product components may itself be eroded by implicit and yet burgeon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(97 citation statements)
references
References 103 publications
(98 reference statements)
6
85
1
1
Order By: Relevance
“…We tested our hypotheses in the empirical setting of Formula 1 (F1), an annual motor racing series in which firms, known as constructors, build cars and hire drivers to race them in Grands Prix around the world. An F1 car is a complex system of interdependent components, including chassis, engine, gearbox, brakes, and electronic control unit (Marino et al, 2015). In line with rules set by the industry's governing body, the Fé dé ration Internationale de l'Automobile (FIA), constructors must build the car chassis in-house but may procure other components from external suppliers.…”
Section: Research Context and Samplementioning
confidence: 99%
“…We tested our hypotheses in the empirical setting of Formula 1 (F1), an annual motor racing series in which firms, known as constructors, build cars and hire drivers to race them in Grands Prix around the world. An F1 car is a complex system of interdependent components, including chassis, engine, gearbox, brakes, and electronic control unit (Marino et al, 2015). In line with rules set by the industry's governing body, the Fé dé ration Internationale de l'Automobile (FIA), constructors must build the car chassis in-house but may procure other components from external suppliers.…”
Section: Research Context and Samplementioning
confidence: 99%
“…First, Gibbons et al [24] empirically preformed a time-lag analysis and found that according to the autocorrelation decay curves, most of the autocorrelation was gone after a lag of 3 or 4 days, whereas some of the autocorrelation was gone from the time series after 1 or 2 days. Second, several peer-reviewed articles [51][52][53][54] found that the human microbiome reaches equilibrium within 10 days following small perturbations to the community. It is imperative to model the di↵erent OTUs in a manner that will fit their temporal patterns.…”
Section: Prediction Accuracymentioning
confidence: 99%
“…In fact, scholars have recently noticed that works in strategic management traditionally lump multiple dimensions of environmental change in one construct, while it would be preferable to have a more fine‐grained understanding of specific dimensions and mechanisms (McCarthy et al, ). As a response, recent works have focused on individual aspects of environmental change such as frequency of change (Posen and Levinthal, ) or magnitude of change (Marino et al, ). Our analysis shows that the effect of technological uncertainty and demand uncertainty is very similar to the effect of the composite index of environmental uncertainty obtained by combining the two dimensions.…”
Section: Discussionmentioning
confidence: 99%